Agents, actors, actorhood : institutional perspectives on the nature of agency, action, and authority - Hwang, Hokyu; Colyvas, Jeannette A.; Drori, Gili S. (Bingley, U.K. : Emerald Publishing Limited, 2019)
National governments are increasingly sharing the stage with many other forms of empowered social actors and authoritative players. Worldwide, alongside governmental bureaucracies, we witness the proliferation of non-for-profit and voluntary associations, business organizations and corporations, civic action committees and political parties, as well as celebrities and cultural icons. Importantly, whether they are individual- and collective social actors, these various actors are bestowed with the legitimate authority to speak their mind, act on their agenda, and influence the course of social progress. How might we conceptualize the role of such empowered social actors?This compilation of research and commentary gathers a range of institutional perspectives investigating what the devolution of state power and the so-called democratization of social action means for the nature of authority and how the multiplicity and variety of social actors impacts societies worldwide, extending from focus on agents to actors to actorhood.
Prelims -- Part I Overview -- Chapter 1: The proliferation and profusion of actors in institutional theory -- Part II Construction of actors -- Chapter 2: What difference does it make?: an institutional perspective on actors and types thereof -- Chapter 3: School principals as agents: autonomy, embeddedness, and script -- Chapter 4: Me and my avatar: acquiring actorial identity -- Chapter 5: Beyond service provision: advocacy and the construction of nonprofits as organizational actors -- Chapter 6: Constructing the consultant as a legitimate actor: the role of active clients in universities -- Chapter 7: Constructing organizations as actors: insights from changes in research designs in the study of institutional logics -- Part III Work of actors -- Chapter 8: Mentoring institutional change: intergenerational construction of meso-structure and the emergence of new logics in American healthcare -- Chapter 9: Machina ex deus?: from distributed to orchestrated agency -- Chapter 10: Political and institutional influences on the legal formation of nascent markets: incorporation of Islamic banking and organic agriculture within the legal system in Turkey, 19842015 -- Chapter 11: Institutional work in high-altitude mountaineering: rope-fixing, the everest brawl' and changes in Sherpa actorhood -- Chapter 12: The claim for actorhood in institutional work -- Part IV Afterword -- Chapter 13: Reflections on rationalization, actors, and others -- Index.
Includes index.
Print version record
Keywords: Organizational sociology -- Research; Authority -- Research; Social Science -- Sociology -- General; Organizational theory & behaviour